Pengaruh Self-Determination Terhadap Keterikatan Relawan (Volunteer Engagement) Pada BAZNAS Kabupaten Banyumas - Sofia Rizky Anindita; Mahardhika Cipta Raharja (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The phenomenon of public participation in volunteer activities without expecting rewards, incentives, or recognition reflects a growing sense of social awareness. Various factors are known to influence volunteer behavior, including social support, altruistic motivation, and personal satisfaction. However, volunteer motivation remains the most frequently studied variable due to its significant role in sustaining volunteer engagement and satisfaction over time. This study aims to examine the influence of Self-Determination Theory on volunteer engagement at BAZNAS Banyumas Regency, focusing on three core components: perceived autonomy, perceived relatedness, and perceived competence. A quantitative approach was employed, with purposive sampling used to recruit 23 active BAZNAS volunteers as respondents. The research instrument was distributed via Google Form, and data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The findings indicate that all three independent variables have a positive and significant effect on volunteer engagement. Among them, perceived relatedness showed the strongest influence, followed by perceived autonomy and perceived competence. These results reinforce the relevance of Self-Determination Theory in explaining volunteer engagement through the fulfillment of basic psychological needs.